THE INFLUENCE OF DIGITAL LEADERSHIP, DIGITAL ORGANIZATIONAL CULTURE TO JOB PERFORMANCE MEDIATION BY WORK ENGAGEMENT IN THE AGROBUSINESS INDUSTRY - Ceisario, Henra; Tyas, Ari Anggarani (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2025)
. The purpose of this study was to identify the influence of Digital Leadership, Digital organizational culture, Work Engagement and Job Performance. Job performance is a measurement of how effective and efficient employees are in completing their tasks. The data analysis method in this study used the Structural Equation Modeling (SEM) method. The population in this study were IT Digital employees who worked in the Agribusiness industry and the sample criteria were selected using the purposive sampling method with the sample criteria being IT employees in the agribusiness industry in Indonesia who had worked for at least 2 years. A questionnaire consisting of 34 statements was distributed to 180 respondents sent via Google Form. Some of the findings in this study are that Digital Leadership and Digital organizational culture have an effect on Work Engagement and Job Performance. However, Work Engagement has not been proven to have an effect on Job Performance, and does not mediate the relationship between Digital Leadership and Digital organizational culture on Job Performance. Digital Leadership will formulate a long-term vision and strategy that includes the use of digital technology. Digital leadership identifies opportunities and directs organizations in adopting relevant technological innovations to achieve business goals. This study is expected to provide valuable insights for the development of management strategies in the agribusiness industry that wants to utilize the potential of digital technology to improve Job Performance